MYH9-Related Thrombocytopenia: Four Novel Variants Affecting the Tail Domain of the Non-Muscle Myosin Heavy Chain IIA Associated with a Mild Clinical Evolution of the Disorder - Zaninetti, Carlo; De Rocco, Daniela; Giangregorio, Tania; Bozzi, Valeria; Demeter, Judit; Leoni, Pietro; Noris, Patrizia; Ryhänen, Samppa; Barozzi, Serena; Pecci, Alessandro; Savoia, Anna (Hämostaseologie, 2019)
MYH9-related disease (MYH9-RD) is an autosomal-dominant thrombocytopenia caused by mutations in the gene for non-muscle myosin heavy chain IIA (NMMHC-IIA). Patients present congenital macrothrombocytopenia and inclusions of NMMHC-IIA in leukocytes, and have a variable risk of developing kidney damage, sensorineural deafness, presenile cataracts and/or liver enzymes abnormalities. The spectrum of mutations found in MYH9-RD patients is limited and the incidence and severity of the non-congenital features are predicted by the causative MYH9 variant. In particular, different alterations of the C-terminal tail domain of NMMHC-IIA associate with remarkably different disease evolution. We report four novel MYH9 mutations affecting the tail domain of NMMHC-IIA and responsible for MYH9-RD in four families. Two variants cause amino acid substitutions in the coiled-coil region of NMMHC-IIA, while the other two are a splicing variant and a single nucleotide deletion both resulting in frameshift alterations of the short non-helical tailpiece. Characterization of phenotypes of affected individuals shows that all of these novel variants are associated with a mild clinical evolution of the disease.
Keywords: inherited platelet disorders; inherited thrombocytopenia; MYH9-related disease; non-muscle myosin IIA